ANALISIS KURIKULUM KEWIRAUSAHAAN UNTUK MODUL PEMBELAJARAN KIMIA DI ERA PANDEMI COVID-19, TOPIK PRODUKTIVITAS IKAN MUJAIR - K Anom W; Wulan Sundari Apriana; Tatang Suhery; Effendi Nawawi; Fuad Abd Rachman (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2022)
The purpose of this study was to describe the curriculum of entrepreneurship courses on the development of integrated learning modules STEM on feed topics to increase the productivity of tilapia fish. This research was conducted on 7th semester students of 2018 class of Chemistry Education, Faculty of Teacher Training and Education, Sriwijaya University. This research method is descriptive, which collects data using interviews, questionnaires and study documentation. The average value of the questionnaire validity test is 0.630 and the questionnaire reliability test is 0.9 with a very good category. The results of this study showed students strongly agreed as much as 60%, agreed as much as 33.3% and hesitated as much as 6.7% developed a module with the topic of feed to increase the productivity of tilapia and included it in the curriculum of the era of the covid-19 pandemic.